1984
DOI: 10.1002/hlca.19840670702
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Stereochemistry of 2‐(Nitromethylidene)‐Heterocycles

Abstract: SummaryThe 'H-NMR spectra of 2-(nitromethy1idene)pyrrolidine (7), l-methy1-2-(nitromethy1idene)imidazolidine (10) and 3-(nitromethy1idene)tetrahydrothiazine (1 1) in CDC1, and (CDJ,SO indicate that these compounds have the intramolecularly H-bonded structures (2)-7, (E)-10 and (2)-11 while the N-methyl derivative 8 of 7 is (E)-configurated in both solvents. 1 -Benzylamino-l-(methylthio)-2-nitroethylene (13), an acylic model, has the H-bonded configuration (E)-13 in CDC1, and in (CD,),SO. 2-(Nitromethy1idene)th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Interestingly, TS17 is 0.9 kcal/mol more stable than intermediate 21 . One can expect that structures 21 and 25 can be interconverted in a dynamic equilibrium (Scheme ) on the basis of the experimental observation of Rajappa et al…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, TS17 is 0.9 kcal/mol more stable than intermediate 21 . One can expect that structures 21 and 25 can be interconverted in a dynamic equilibrium (Scheme ) on the basis of the experimental observation of Rajappa et al…”
Section: Resultsmentioning
confidence: 99%
“…Activation barriers of the rate-determining steps (WE and CTI) of chosen paths (3 and 5) were predicted to be 31.9 and 29.0 kcal/mol, respectively, by B3LYP/6-31+G**. In order to see how other computational methods would affect these barriers, B3LYP/6-31+G** was compared to the PBE1PBE, BLYP, B3PW91, MPW1PW91, MPW1K, and MP2(SP) methods by using 6-31+G** and different basis sets (6-31G*, 6-31G**, and 6-31++G**) with B3LYP.…”
Section: Resultsmentioning
confidence: 99%
“…in a geometrically favorable position for the formation of intramolecular H-bonding, as in 3c-Z isomer, was previously reported for similar compounds. 2 The 1 H NMR analysis revealed that 3c undergoes further chemical transformation with time (vide infra) in the reaction medium, which is acidic due to the evolution of HBr. However, on a preparative scale, rapid a-bromination (~10 min) of 2a-c-Z at r.t., in alcohol or in boiling CCl 4 as a solvent (Scheme 1), resulted due to the lower solubility, in isolation of the primary bromination compounds 3a-c in good yields of 60.5-66%.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] These compounds, bearing the electron-donor and acceptor groups at the termini of the double bond, are of interest not only for their mechanistic properties, [5][6][7] but also as versatile synthetic intermediates. 4,8 Synthetic routes to a number of such compounds have been described.…”
mentioning
confidence: 99%
“…In recent years, numerous studies of push-pull alkenes have been reported. [1][2][3][4] These compounds, bearing the electron-donor and acceptor groups at the termini of the double bond, are of interest not only for their mechanistic properties, [5][6][7] but also as versatile synthetic intermediates. 4,8 Synthetic routes to a number of such compounds have been described.…”
mentioning
confidence: 99%